RNA-Binding Specificity of the Human Fragile X Mental Retardation Protein. Issue 13 (12th June 2020) - Athar, Youssi M.; Joseph, Simpson
Abstract: Fragile X syndrome is the most common form of inherited intellectual disability and is caused by a deficiency of the fragile X mental retardation protein (FMRP) in neurons. FMRP regulates the translation of numerous mRNAs within dendritic synapses, but how FMRP recognizes these target mRNAs remains unknown. FMRP has KH0, KH1, KH2, and RGG domains, which are thought to bind to specific RNA recognition elements (RREs). Several studies used high-throughput methods to identify various RREs in mRNAs that FMRP may bind to in vivo . However, there is little overlap in the mRNA targets identified by each study, suggesting that the RNA-binding specificity of FMRP is still unknown. To determine the specificity of FMRP for the RREs, we performed quantitative in vitro RNA binding studies with various constructs of human FMRP. Unexpectedly, our studies show that the KH domains do not bind to the previously identified RREs. To further investigate the RNA-binding specificity of FMRP, we developed a new method called M otif Id entification by A nalysis of S imple sequences (MIDAS) to identify single-stranded RNA sequences bound by KH domains. We find that the FMRP KH0, KH1, and KH2 domains bind weakly to the single-stranded RNA sequences suggesting that they may have evolved to bind more complex RNA structures. Additionally, we find that the RGG motif of human FMRP binds with a high affinity to an RNAG-quadruplex structure that lacks single-stranded loops, double-stranded stems, or junctions. Graphical abstract: Unlabelled Image Highlights: FMRP KH domains do not bind to several reported RNA sequence motifs. Developed a new method, MIDAS, to identify ssRNA sequences that bind to FMRP KH domains The KH domains of human FMRP bind with low affinity to ssRNA, unlike canonical KH domains. RGG motif of FMRP binds with high affinity to an RNAG-quadruplex structure that does not contain single-stranded loops, double-stranded stems, or junctions.